Konflik Batin Tokoh dalam Cerpen “Cinta Semata Wayang” Melalui Perspektif Psikoanalisis Freud - Selviah Selviah; Nori Anggriani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study analyzes the short story Cinta Semata Wayang by Nuryana Asmaudi SA using a literary psychology approach grounded in Sigmund Freud’s psychoanalytic theory. The research applies a literature study with a descriptive qualitative method. Data were collected through close reading to identify structural elements and the psychological dynamics of the characters. The findings reveal marital conflict symbolized through wayang figures, particularly Rama and Sinta. Structurally, the story presents a progressive plot, symbolic and metaphorical language, and central themes of love and responsibility. The psychological analysis highlights the interaction of the id, ego, and superego within the main characters: Rama experiences tension between personal desires and moral norms, while Sinta demonstrates superego dominance through loyalty and emotional endurance. The short story emphasizes that true love is not solely based on emotion but also requires responsibility, commitment, and moral awareness as the foundation of a harmonious and sustainable relationship. This research contributes to literary psychology studies and deepens understanding of moral values in literature.